1993
DOI: 10.1016/0920-5632(93)90177-8
|View full text |Cite
|
Sign up to set email alerts
|

Chiral gauge theories and fermion-Higgs systems

Abstract: The status of several proposals for defining a theory of chiral fermions on the lattice is reviewed and some new estimates for the upper bound on the Higgs mass are presented.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
36
0

Year Published

1993
1993
2003
2003

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(36 citation statements)
references
References 61 publications
0
36
0
Order By: Relevance
“…Where available, it was always found that the true fermion spectrum is vectorlike (see ref. [7,9,43] for details).…”
Section: A the Robustness Of The No-go Theoremsmentioning
confidence: 99%
See 1 more Smart Citation
“…Where available, it was always found that the true fermion spectrum is vectorlike (see ref. [7,9,43] for details).…”
Section: A the Robustness Of The No-go Theoremsmentioning
confidence: 99%
“…(This applies to many other chiral fermion proposals, see ref. [7,9].) In the second part of this paper, we examine the dynamics of the lattice longitudinal modes from a broader point of view.…”
Section: Introductionmentioning
confidence: 99%
“…The actual fermion spectrum can then be different from the naively expected one, and come out vectorlike rather than chiral. This is precisely what happens in many proposals which have been considered to date (for reviews, see [1]). …”
Section: Introductionmentioning
confidence: 95%
“…2 is a possible interpolation between the limits M = ±∞ and F 2 π = ∞, partly inspired by the phase diagram of the Smit-Swift model and other related Higgs-Yukawa models [62][63][64]. Attempts to construct chiral gauge theories as the continuum limit of such lattice models have failed because it was impossible to remove the doubler fermions, both at weak and at strong Yukawa couplings [65]. Such problems do not affect our construction of lattice effective theories with nonlinearly realized chiral symmetry because, in that case, there is no need to approach a second order phase transition to extract low-energy continuum physics.…”
Section: From the Chiral Quark Model To Qcd?mentioning
confidence: 99%